Exploring Erasmus student mobility in Ukraine: A case study - Baranchenko, Yevhen; Yukhanaev, Andrey; Patoilo, Pedro (Journal of Eastern European and Central Asian Research (JEECAR), 2016)
In the context of increasing interest in the internationalisation of education, the Erasmus programme of student mobility led by the European Commission is perceived as a highly desirable by many stakeholders. Despite the high demand emanating from Ukrainian students for Erasmus programme participation, the inward student mobility of EU nationals to Ukraine remains exceptionally low at the undergraduate level. The main aim of the current study is to explore the inward Erasmus student mobility mechanism in Ukraine through application of the single case study approach. The data were collected through participant observation, two rounds of interviews and the analysis of the participant diary. The research outcomes shed light on how the inward Erasmus student mobility programme in Ukraine can be arranged more effectively. We identified four broad areas by means of thematic analysis, which includes transparency of the process; communication; living conditions; learning process and facilities.